The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/pro.3096
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of divergent SEA domains in cell surface proteins and nucleoporin 54

Abstract: SEA (sea urchin sperm protein, enterokinase, agrin) domains, many of which possess autoproteolysis activity, have been found in a number of cell surface and secreted proteins. Despite high sequence divergence, SEA domains were also proposed to be present in dystroglycan based on a conserved autoproteolysis motif and receptor-type protein phosphatase IA-2 based on structural similarity. The presence of a SEA domain adjacent to the transmembrane segment appears to be a recurring theme in quite a number of type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 97 publications
0
37
0
Order By: Relevance
“…1 ). A SEA (for Sperm protein, Enterokinase and Agrin) domain is located in the C-terminal part of AMN directly preceding the transmembrane helix 17 . The SEA domain has a classic βαββαβ-fold 18 found in various types of proteins including initiation and elongation factors 19 .…”
Section: Resultsmentioning
confidence: 99%
“…1 ). A SEA (for Sperm protein, Enterokinase and Agrin) domain is located in the C-terminal part of AMN directly preceding the transmembrane helix 17 . The SEA domain has a classic βαββαβ-fold 18 found in various types of proteins including initiation and elongation factors 19 .…”
Section: Resultsmentioning
confidence: 99%
“…1 A). For PCDH15, this domain has also been labeled as extracellular linker (EL) (49), protocadherin-15 interacting-channel associated domain (PICA) (48), or sea urchin sperm protein, enterokinase, agrin (SEA) like domain (54)(55)(56). PCDH24 has a similar putative MAD, whereas FAT and CELSR cadherins all have ''unknown'' domains between their cadherin repeats and additional extracellular domains with predicted EGF, EGF-like or LamG folds (details below).…”
Section: Introductionmentioning
confidence: 99%
“…As its name implies, the canonical SEA domain was first detected in sea urchin sperm protein, and in EK and agrin proteins also, but its function is not well understood, except that it is known to be involved in the autoproteolysis that causes subsequent functional domains to be shed or the protein to be degraded, and it also has an effect on the carbohydrate chains nearby it (List et al, 2006 ). Recent advanced search programs have shown that many molecules contain the SEA domain, including some mucins, glycans, phosphatases, and cadherins (Pei and Grishin, 2017 ). Because the 90-bp exon of EK-X2 is inserted immediately before the autoproteolysis motif in EK, it may affect some EK functions as yet unknown or contribute a new function for the SEA domain.…”
Section: Discussionmentioning
confidence: 99%